Luo Bo's adventure - Kwang, Yuan Xin (Nanyang Technological University, 2022)
Luo Bo’s Adventure is a 3-D open world indie adventure role playing game that is set in sunny island Singapore, where the player plays as Luo Bo, a chef bunny who arrives at Singapore to meet her grandmother whom she calls Ah Ma. This project is designed to introduce and pay tribute to some of Singapore’s local delights through gameplay and simultaneously explore ways to create an immersive gameplay without heavy game controls.